Struktur Kepribadian Tokoh Utama dalam Cerpen Pantaskah Aku Bahagia Karya Arta Tri Wahyuningsih: Tinjauan Psikologi Sastra - Lustin, Lusthin Tendri (Universitas Swadaya Gunung Jati, 2024)
This study aims to describe the personality structure of the main character in the short story Pantaskah Aku Bahagia by Arta Tri Wahyuningsih. This is a qualitative descriptive study and falls under the category of library research, using literary psychology theory as its analytical framework. Data were collected by repeatedly reading the short story and taking notes on aspects relevant to the research focus. The results show that the story follows a chronological (progressive) plot. Based on the analysis, the main character’s personality structure consists of the id, ego, and superego within the character Welastri. The impulses of Welastri's id are fulfilled through the ego’s response, which is guided by the superego's considerations. The id is reflected in Welastri’s strong determination to find her biological mother. The ego is evident when Welastri discovers that her biological mother—whom she had been searching for—is actually the mother of her friend, Sofyan, and had already passed away by the time she found out. The superego is shown when Welastri tries to find out about her biological mother secretly, without her foster parents (Abi and Umi) knowing, allowing her to uncover the truth. The conclusion of this study is that the three elements of the main character’s personality work synergistically to shape her into a courageous and optimistic individua